1999
DOI: 10.1063/1.124101
|View full text |Cite
|
Sign up to set email alerts
|

Reactive ion etch-induced effects on the near-band-edge luminescence in GaN

Abstract: GaN grown on c-plane sapphire substrates has been reactive ion etched successfully in a SF 6 plasma with an etch rate of 29 nm/min. The etch rate does not change with substrate temperatures between 10 and 50°C. Optical transitions have not been destroyed after etching, instead, two additional lower energy transitions appear close to the band-edge luminescence. The two additional transitions are related to defect states that bind excitons. The defect-bound states exhibit different behavior compared to the free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…12 An etch rate of 29 nm/min is measured. To define the nanopatterns on the GaN, double layer poly͑methy͒methacrylate ͑PMMA͒ resist and standard lift-off techniques have been used.…”
Section: Methodsmentioning
confidence: 99%
“…12 An etch rate of 29 nm/min is measured. To define the nanopatterns on the GaN, double layer poly͑methy͒methacrylate ͑PMMA͒ resist and standard lift-off techniques have been used.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 Previous works have mainly focused on the plasma-induced effects on the optical properties of GaN films by using various ex-situ physical measurements after the etching. 5,6 The in-situ observation of optical luminescence of the GaN film in the plasma condition has seldom been reported, because the plasma usually contains high energy electrons and exhibits sharp luminescence with wide range of the wavelengths. In our previous study, we have developed an in-situ observation method under plasma conditions and have gotten full photoluminescence (PL) spectra of n-type GaN even under the high-power plasma conditions.…”
mentioning
confidence: 99%
“…It appears that further experiments are needed in order to clarify the exact nature of this PL using low-temperature PL measurements with an emphasis on analyzing the dependence of PL peak intensity on the excitation power. Similarly, Cheung et al [34] reported the appearance of two lower energy transitions close to the band-edge luminescence in etched material, were likely associated with defects states. The intensity ratio of the band-edge PL peak and the donorand/or acceptor-related PL band is presented in Table 1 (UVPL/BL), in particular, there is a maximum intensity of donors and/or acceptors related PL band on the facet of nanotube.…”
Section: Resultsmentioning
confidence: 95%